Comparison of a simple model of dorsal column axons with the electrically evoked compound action potential. Issue 2 (25th May 2018) - Parker, John L; Laird-Wah, James; Cousins, Michael J
Computational modeling has provided insights into the electrophysiological mechanisms of spinal cord stimulation. The models are complex and conclusions drawn from them are only as valid as their assumptions and choice of parameters. Model validation has proved difficult due to lack of direct electrophysiological evidence for comparison. Here, we compare an axon model with measurement of the compound action potential response of dorsal columns axons of the sheep spinal cord. The extracellular potential is calculated from a simple single axon and rather than repeating this calculation for multiple fibers of different sizes and positions, we instead estimate the single fiber response from the ECAP measurements. The single fiber potential is derived from ECAP by reversing the effect of propagation from the stimulation site. We used literature values for the ion channel properties for sensory neurons and the axon model predicts the shape of the ECAP-derived single fiber action potential remarkably well.